An Analysis of Imagery Found in Novel “The Midnight Library” by Matt Haig in 2020 - Al Amin, Merdeka Putri Khafidhotur Rohmah; Oktariza, Dodi; Efendi, Dedi (Krinok:Jurnal Linguistik Budaya, 2024)
This research aims to analyze the imagery in the novel "The Midnight Library" by Matt Haig. The purpose of this study are 1) to Analyze the Types of Imagery by Perrine and Thomas's Theory found in the Novel “The Midnight Library” By Matt Haig In 2020, 2) to Explain the Function of Imagery found in the Novel “The Midnight Library ” By Matt Haig In 2020.In conducting this research, the method used is descriptive qualitative by Hancock (2002: 2). The results of research found by researcher were 476 imagery consisting of 149 visual imagery data, 44 auditory imagery data, 144 kinesthetic imagery data, 36 tactile imagery data, 8 olfactory imagery data, 12 gustatory imagery data and 83 organic imagery data. The imagery function in this novel has also been categorized into 3 functions, namely 1) Freshness 2) Intensity and 3) Evocative power. However, the researcher decided to summarize and explain 35 total imagery that have been found in the novel. The other imagery that are not discussed in depth in this study have been included in the appendix as a complement.From the data shown, visual imagery is the most common imagery found in the midnight library novel followed by the kinesthetic imagery addition, this study also revealed that Evocative Power is the most dominant function in this novel. Evocative power or evociation refers to the ability of a text to arouse a deep emotional reaction or a picture that lives in the mind of the reader. The Midnight Library utilizes this inspiring power effectively to attract readers into the narrative world, and convey important themes such as regret, life choices, and the search for meaning